Plan de negocio para crear una microempresa productora y comercializadora de leche de soya, cantón Quevedo, año 2013 - Toledo Paredes, Laura Fernanda (2014)
This work-study Business Plan to create a micro producer and marketer of soy milk, was developed in the canton Quevedo between its urban and rural parishes. It was necessary to determine the sample size (384), the same could extract the potential universe of consumers soymilk. The research was conducted in order to determine the feasibility of developing a business plan to produce and sell soy milk. It took listening to the discretion of the county society, and their results were very optimistic. The sample size allowed us to learn that 55% would like to consume soy derivative, such as milk; this new universe and reformulated the questions raised and the same optimistic responses yielded information regarding the installation of micro processing of soymilk. The study likewise led to determine the best path for operation of the plant, is located at km 55 of the road Quevedo - Good Faith and the potential consumer market is 211 representing 55 % of the sample 384 which constitute 183,656 and the 55% is 101,010 habitants of all genres and ages. The population is growing steadily, and in the future will increase; and of them all, a large percentage of consumers will soymilk. All human beings engaged in consumption of goods and products of animal and vegetable origin; Soy has the best nutritional characteristics; therefore, the optimism of the production and sale of soymilk, would become excellent investment space. The return on investment is guaranteed. The VAN is highly positive; the TIR exceeds the discount rate, and the benefit ratio - the cost is 2.06 which puts it in the best safe alternative for the investor and insurance growth projections